The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1016/j.yqres.2013.03.002
|View full text |Cite
|
Sign up to set email alerts
|

A raised OIS 3 sea level recorded in coastal sediments, southern Changjiang delta plain, China

Abstract: Q. (2013). A raised OIS 3 sea level recorded in coastal sediments, southern Changjiang delta plain, China. Quaternary Research, 79 (3), 424-438. A raised OIS 3 sea level recorded in coastal sediments, southern Changjiang delta plain, China AbstractThe distribution of marine-influenced oxygen isotope stage (OIS) 5 to OIS 1 sediments was examined in several late Quaternary boreholes from the southern Changjiang (Yangtze) delta plain, China, using different dating methods including OSL, U-series, AMS 14C and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 67 publications
(99 reference statements)
1
27
0
Order By: Relevance
“…Both sites are affected because the river sediments are carried south along the coast once they reach the ocean, as part of a belt that extends for more than 1000 km (Liu et al 2018). The outer Changjiang Delta has been subsiding at a rate of 1-2 mm a -1 since MIS 5 (Fang 1959;Huang 1959;Yu 1959;Li et al 2000;Wang et al 2013), and continental shelf sediments opposite the Oujiang Delta are Figure 8 Age-depth relationships of the MIS 3 (YQ0901 and YQ0902) paleosols and the Early Holocene (YQ0903 and YQ0904) paleosols, compared to relative sea level for the past 40 ka. The dark blue curve is the ice-volume equivalent sea level curve of Lambeck et al (2014).…”
Section: Discussionmentioning
confidence: 99%
“…Both sites are affected because the river sediments are carried south along the coast once they reach the ocean, as part of a belt that extends for more than 1000 km (Liu et al 2018). The outer Changjiang Delta has been subsiding at a rate of 1-2 mm a -1 since MIS 5 (Fang 1959;Huang 1959;Yu 1959;Li et al 2000;Wang et al 2013), and continental shelf sediments opposite the Oujiang Delta are Figure 8 Age-depth relationships of the MIS 3 (YQ0901 and YQ0902) paleosols and the Early Holocene (YQ0903 and YQ0904) paleosols, compared to relative sea level for the past 40 ka. The dark blue curve is the ice-volume equivalent sea level curve of Lambeck et al (2014).…”
Section: Discussionmentioning
confidence: 99%
“…Since the Late Pleistocene, three large-scale transgressions have occurred, and the highest global sea level took place in the MIS5 stage in eastern China (Liu et al, 2009(Liu et al, , 2010Wang et al, 2013 (Jacobs, 2008).…”
Section: Chronostratigraphic Framework Of the Corementioning
confidence: 99%
“…The black and white intervals represent normal and reversed polarities, respectively. Liu et al (2016a) only by the global sea-level change, but also by multiple sea-land lifting (Wang et al, 2013;Yu Ge et al, 2016), glacial isostatic adjustment (Yu et al, 2007), and sediment compaction (subsidence) (Edwards et al, 2000). A large-scale transgression occurred during the Holocene in eastern China, which affected the Yangtze River Delta and the majority of the Subei Basin.…”
Section: Regional Comparison Of Large-scale Transgressions In the Wesmentioning
confidence: 99%
“…The second is the mechanism of transgression during MIS 3 and MIS 5 in the SYS. Sediment records in the coastal area of the SYS showed that the MIS 3 marine transgression deposits were found to be significant (Wang et al, 1981;Lin et al, 1989;Zhao et al, 2008;Zhang et al, 2010;Wang et al, 2013), while the records of the transgression sediments during MIS 5 seemed to be sporadic (Wang et al, 1981;Zhao et al, 2008). Since the sea levels during MIS 5 were considered to be higher than MIS 3 ones (Chappell and Shackleton, 1986), why did the sedimentary records in the SYS suggest that transgression during MIS 3 was generally more significant than that during MIS 5 (Wang et al, 1981)?…”
Section: -7×10mentioning
confidence: 99%
“…In addition, MIS 3 transgression events were widely reported based on many cores drilled from both deltaic plain (c.f. Zhong et al, 1999;Zhao et al, 2008;Zhang et al, 2010;Wang et al, 2013) and offshore borehole cores (c.f. Zhu et al, 1999;Li et al, 2013;Xia et al, 2013;Wang et al, 2014;Ji et al, 2015;Sun et al, 2015) in the SYS ( Figure 5).…”
Section: Comparison Of Mis 3 and Mis 5 Marine Sedimentsmentioning
confidence: 99%